Protective Effects of Wogonin against Alzheimer's Disease by Inhibition of Amyloidogenic Pathway. (7th June 2017) - Huang, Ding-Siang; Yu, Yu-Chen; Wu, Chung-Hsin; Lin, Jung-Yaw
Abstract : One of the pathogenic systems of Alzheimer's disease (AD) is the formation of β -amyloid plaques in the brains of patients, and amyloidogenic activity becomes one of the therapeutic targets. Here, we report wogonin, one of the major active constituting components in Scutellaria baicalensis, which has the neuroprotective effects on amyloid- β peptides- (A β -) induced toxicity. Oral wogonin treatment improved the performance of triple transgenic AD mice (h-APPswe, h-Tau P301L, and h-PS1 M146V) on the Morris water maze, Y-maze, and novel object recognition. Furthermore, wogonin activated the neurite outgrowth of AD cells by increasing neurite length and complexity of Tet-On A β 42 -GFP SH-SY5Y neuroblastoma cells (AD cells) and attenuated amyloidogenic pathway by decreasing the levels of β -secretase, APP β -C-terminal fragment, A β -aggregation, and phosphorylated Tau. Wogonin also increased mitochondrial membrane potential (∆ ψ m) and protected against apoptosis by reducing the expression of Bax and cleaved PARP. Collectively, these results conclude that wogonin may be a promising multifunctional drug candidate for AD.